Sistem Pertahanan Berlapis Benteng Willem I Ambarawa - Nurmala, Siti; Arafat, Argi (Department of Archaeology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
The defense system of a fortress is a crucial aspect of military strategy aimed at protecting territories or strategic assets from external attacks. The Willem I Ambarara Fortress was constructed with the application of complex architectural designs and considerations of geographical location, intending to maximize the utilization of surrounding defense strengths. The method employed was qualitative descriptive analysis with geographic analysis, encompassing literature review, exploration of secondary data, and direct observations at the Willem I Fortress. The research findings indicate that the Willem I Fortress possesses a complex and layered defense strategy, leveraging natural topography and strategic positioning to establish formidable defenses. This defense strategy creates a fortress that is challenging for enemies to breach, with comprehensive facilities to support troop life and operations. === Sistem pertahanan benteng merupakan aspek penting dalam strategi militer yang bertujuan untuk melindungi wilayah atau aset strategis dari serangan luar. Benteng Willem I Ambarara dibangun dengan penerapan desain arsitektur yang kompleks dan pertimbangan letak geografis, serta dibangun guna memanfaatkan kekuatan pertahanan sekitar secara maksimal. Metode yang digunakan yaitu deskriptif kualitatif dengan analisis geografis, mencakup studi pustaka, eksplorasi data sekunder, dan observasi langsung di Benteng Willem I. Hasil penelitian menunjukkan bahwa Benteng Willem I memiliki strategi pertahanan yang kompleks dan berlapis, dengan memanfaatkan topografi alam dan posisi strategis menjadikan Benteng Willem I memiliki pertahanan yang kuat. Strategi Pertahanan ini menciptakan benteng yang sulit ditembus oleh musuh, dengan dukungan fasilitas lengkap untuk mendukung kehidupan dan operasional pasukan.